2008
DOI: 10.24832/kapata.v4i6.92
|View full text |Cite
|
Sign up to set email alerts
|

Arkeologi Nusa Tenggara Timur dan Masa Depan

Abstract: No Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…The research on the success of AI with frozen semen carried out in Polewali Mandar regency, West Sulawesi Province, namely in Wonomulyo and Tinambung districts also showed a Conception Rate (CR) of 78% and a Service Per Conception (S/C) of 1.5 which was a very high value for AI services good, a good S/C value is 1.6-2.0 while other factors that influence the success of AI are the type of parent 85%, Body Scoring Condition (BSC) 83%, AI implementation time includes 82% estrus, inseminator skills 81 %, and skills of farmers in detecting estrus 80% [18]. The results of a similar study conducted by [19] showed the success rate of AI in East Halmahera in three villages, namely Bumirestu, Dakaino, and Akedaga villages with S/C, CR and CvR values as follows (1.08; 92.5%; 87%), (3.33; 71%; 25%) and (5.71; 70%; 10%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The research on the success of AI with frozen semen carried out in Polewali Mandar regency, West Sulawesi Province, namely in Wonomulyo and Tinambung districts also showed a Conception Rate (CR) of 78% and a Service Per Conception (S/C) of 1.5 which was a very high value for AI services good, a good S/C value is 1.6-2.0 while other factors that influence the success of AI are the type of parent 85%, Body Scoring Condition (BSC) 83%, AI implementation time includes 82% estrus, inseminator skills 81 %, and skills of farmers in detecting estrus 80% [18]. The results of a similar study conducted by [19] showed the success rate of AI in East Halmahera in three villages, namely Bumirestu, Dakaino, and Akedaga villages with S/C, CR and CvR values as follows (1.08; 92.5%; 87%), (3.33; 71%; 25%) and (5.71; 70%; 10%).…”
Section: Resultsmentioning
confidence: 99%
“…In order to produce high-quality cattle quickly and in huge numbers while employing as many excellent males as feasible, artificial intelligence (AI) has been successful in enhancing the genetic quality of livestock. AI stands in stark contrast to embryo transfer, which has been shown to improve genetic quality and to stop or slow the development of illnesses brought on by interracial relationships [18]. AI can prevent the transmission of illnesses brought on by direct physical touch as well as the spread of other pathogens such as parasitic and harmful bacteria, viruses, and protozoa through contact [13].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Selain itu, tingkat pendidikan memiliki korelasi yang kuat dengan perilaku, khususnya berperilaku dalam hal kesehatan. Hal ini didukung oleh hasil penelitian yang dilakukan oleh Kusumawati, et. al (2008)…”
unclassified